Moving People to Deliver Services : How Can the WTO Help? - Chaudhuri, Sumanta; Mattoo, Aaditya; Self, Richard (World Bank, Washington, DC, 2013)
The previous General Agreement on Trade in Services (GATS) negotiations produced little liberalization of the movement of individual service providers (mode 4), and the potentially large global gains from such movement remain unrealized. In the current negotiations, as part of the Doha Development Agenda, developing countries are seeking greater openness in their area of comparative advantage: the movement of providers unrelated to commercial presence abroad. At the same time, many multinational firms would like easier intra-corporate movement of their personnel. We describe how this coincidence of interest could be harnessed to deliver greater openness at least for skilled service providers.